Christ meets me everywhere: Augustine's early figurative exegesis - Cameron, Michael (Oxford studies in historical theology, 2012)
This book studies the earliest biblical reading practices of Augustine of Hippo (354-430), the greatest of the Latin Church Fathers. It examines works from the first fifteen years of Augustine's Christian life in order to follow the course of his development. His reflections on the craft of hermeneutics advanced not only specifically theological reading practices but also the humane art of textual interpretation. Augustine's rationale for figurative reading in the tens of thousands of Scripture references that filled hundreds of sermons, letters, and treatises made him the most widely read commentator on the Christian Scriptures in the west for more than a thousand years